Rancang Bangun Sistem Informasi Pengelolaan Penyewaan Kamera Berbasis WEB - Sujana, Faris Syafiq; Huda, Yasdinul (Universitas Negeri Padang, 2022)
This research is based on problems in the management of information and data that still use manual methods at Highspeed Studio. Highspeed Studio is a business engaged in the field of camera rental and other photographic equipment. The purpose of this research is to design and build a website-based system, where information and rental processes can be done and managed properly and efficiently. The method used in this study is waterfall method which consists of several stages including: (1) needs analysis, (2) application and system design, (3) implementation, (4) testing, and (5) maintenance. The results of this study provide effectiveness in the process of booking far away (booking) on goods that will be rented, and provide information related to rental activities that have been done within a certain period of time.